Adapting the Short Form of the Internet Gaming Disorder Scale into Turkish: Validity and Reliability - Aricak, Osman Tolga; Dinc, Mehmet; Yay, Mahmut; Griffiths, Mark D.; Dinç, Mehmet; Arıcak, Osman Tolga (TURKISH GREEN CRESCENT SOC, 2018)
The nine-item Internet Gaming Disorder Scale - Short Form (IGDS9-SF) is one of the most popular instruments developed based on DSM-5 to assess gaming addiction internationally. Given the number of common instruments to assess and diagnose gaming disorder cross-culturally, validity and reliability studies of instruments such as the IGDS9-SF have become more important. Therefore, the aim of the present study was to adapt and examine psychometric properties of IGDS9-SF in Turkish. A total of 455 participants aged between 10 and 29 years were recruited to take part in the present study. Validity of the IGDS9-SF was assessed in two ways: confirmatory factor analysis (CFA) and criterion-related validity. CFA revealed that IGDS9-SF was unidimensional. A significant correlation between IGDS9-SF and Internet Addiction Scale indicated criterion-related validity. One supportive finding for the validity was the significant difference found between the upper and lower 27-percentile groups in terms of IGDS9-SF scores. The IGDS9-SF also showed satisfactory levels of reliability using Cronbach's alpha (.82), Guttman's split-half (.75), and test-retest reliability coefficient (.78). It is concluded that the IGDS9-SF appears to be a valid and reliable scale to assess IGD among Turkish adolescents and young adults.
Keywords: Internet gaming disorder; Gaming addiction; Online gaming; Computer games; Video games; Adolescents; Young adults